A non-invasive method for verification of acute mesenteric blood flow disorder - Magomed D. Dibirov; Rasul U. Gadzhimuradov; Igor P. Parfenov; Darya I. Sidorova; Vladimir S. Fomin (Clinical Medicine (Russian Journal), 2026)
Acute mesenteric perfusion disorder (AMP) is a critical emergency condition characterized by a sudden reduction in blood flow through the mesenteric vessels to the intestine, leading to inadequate perfusion of the small intestine. Mortality from this pathology ranges from 50% to 97% and is primarily due to its rapid progression and subsequent development of intestinal necrosis. Diagnosis of AMP and intestinal ischemia remains a challenge for clinicians due to the lack of pathogmonic symptoms of the disease. In the context of early diagnosis of acute vascular injury of the small intestine, new laboratory markers, in particular the intestinal form of fatty acid binding protein (Intestinal Fatty-Acid Banding Protein, I-FABP), can help identify patients at risk, monitor disease progression and make decisions about treatment or a particular treatment strategy. I-FABP is a cytosolic protein with a molecular weight of 15 kDa. We present a clinical observation of a successful non-invasive method for early diagnosis of AMP in a 65-year-old patient, which allowed us to optimize surgical tactics and achieve a cure for this complex pathology.